T.QAYÍPBERGENOV POVESTLERINDE KÓRKEM DETALDÍŃ ESTETIKALÍQ XÍZMETI - Sarsenbaev, Q.J. (SCIENCE and SOCIETY, 2025)
The article examines in detail the aesthetic function of artistic details in the stories of the writer T.Kayipberganov.